When “I” or “S/He” uses the product: the impact of narrative perspective on consumers’ brand attitudes in storytelling ads - Chen, Tingting; Fan, Xinqiao; He, Jiayu; Fan, Jun; Chen, Wei (Frontiers in Psychology, 2024)
Storytelling ad is presented from one or more narrative perspectives. Narrative perspective, which can alter the way in which the plot is physiologically or psychologically perceived, can significantly affect consumer experience. This study conducts three experiments with 526 participants to analyze the influencing mechanism of narrative perspective (first-versus third-person) on consumers' brand attitudes in storytelling ads of products with different involvement (high versus low). The research results are as follows: (a) Narrative perspective (first-versus third-person) exerts persuasive effects on consumer brand attitudes; (b) Processes of social presence and self-brand connection explain the effects of narrative perspective on brand attitudes; (c) When product involvement is high, the use of the firstperson narrative perspective in storytelling ads will result in a more positive brand attitude than the use of third-person narrative will; With lower product involvement, there is no significant difference in the impact on brand attitudes regardless of narrative perspective (first-person versus third-person). This research finds that different narrative perspectives significantly impact the persuasiveness of advertising. Boundary conditions exist for the effect of narrative persuasion, and product involvement moderates the effect of narrative perspective on brand attitudes.